Managing Cognitive Load in Invertebrate Classification: CLT-Based Notecard Learning Media - Indri Annisa; Danang Budi Setyawan; Adhi Susilo; Leonard Raden Hutasoit (Biosel Biology Science and Education, 2026)
Learning invertebrate classification requires intensive interactivity that often overloads students’ working memory and leads to superficial understanding. From a Cognitive Load Theory (CLT) perspective, this issue is worsened by instructional media with complex, unfocused visuals that increase extraneous cognitive load. This study developed and evaluated a CLT-based notecard media to manage cognitive load and support meaningful schema construction. Using an R&D approach, the study included needs analysis, CLT-informed design, expert validation, and limited field testing with 39 senior high school students. Data was collected through expert validation instruments, analysis of students’ classification records, Paas mental effort ratings, and qualitative responses. Results indicate that the CLT-based notecard media align with CLT principles and are feasible for instructional use, although refinements are needed to improve readability and visual signaling. Students’ mental effort levels were generally low to moderate, suggesting that the media may provide manageable cognitive support during classification tasks. Overall, the findings suggest that CLT-based notecard learning media may support early observation and initial schema development in biological classification learning.  Keywords: Cognitive Load Theory, Invertebrate Classification, Notecard Learning Media, Schema Construction, Working Memory